Spectrophotometric evaluation of shade selection with digital and visual methods - S Preethi Suganya; P Manimaran; D Saisadan; C Dhinesh Kumar; D Abirami; V Monnica (Wolters Kluwer Medknow Publications, 2020)
Aim: The main purpose of the study was to learn the possible shade differences between human eye and the digital method with spectrophotometric methods. Materials and Methods: Fifty dental students of age groups 18-25 with maxillary right central incisor after undergoing oral prophylaxis were included in this study. Before undergoing shade selection, standardization protocol was followed. The shade of the right maxillary central incisor was determined by using the following methods: visual, spectrophotometer, and digital photography. The shades obtained by both spectrophotometer and visual methods are compared and similarly LFNx01, aFNx01, and bFNx01 values obtained by both spectrophotometer and digital methods are compared. Finally these comparisons are subjected to statistical analysis. Results: Z and P values of digital and spectrophotometric methods were found to be statistically significant. Tooth shade selected between spectrophotometric and visual method was analyzed by using chi-square test, which shows highly significant value. Conclusion: It was concluded that the digital photography can be used as one of the reliable methods for shade selection in a clinical setup.